Inflaç\~ao, desemprego e choques cambiais: Estimativas var para a economia brasileira - Bernardo Patta Schettini; Raphael Rocha Gouvea; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– We estimate a VAR model of the Phillips curve with an exchange rate shock to the Brazilian economy. Several different specifications, with different time frequencies, were estimated. Overall the results were robust to these changes, and can be summed up in the following: i) the pass-through to the next month inflation is around 0.04 percentage points (p.p.) (0.48 p.p. over the annualized inflation); ii) a shock on the unemployment rate lasts for 18 months; iii) a shock on the expectations are carried to the next month inflation (0.58 p.p. over the annualized inflation); and iv) a shock on the inflation rate has no effect over the unemployment rate. That is, more inflation does not reduce unemployment.
Keywords: E31; E24; C32; 330; Phillips-Kurve; VAR-Modell; Wechselkurs; Schock; Brasilien